Nos lieux interdits . Our Forbidden Places - Kilani, Leila (CDP/INA, 2008)
Verzio FF Submission Between 2004 and 2007, journalist Leila Kilani followed the lives of four families making their way through Morocco's Equity and Reconciliation Commission (ERC, the equivalent to South Africa's Truth and Reconciliation Commission), set up to investigate state-sponsored disappearances between 1956 and the end of the 1980s. The ERC received over 30,000 applications when it opened in 2004. From young Zaynab, seeking the truth about her grandfather, to elderly ex-prisoner Hassan, these are gripping stories. Leila Kilani's three-year investigation into Morocco's hidden and tumultuous past is blended into this documentary.